(untitled) (Asia Pacific Journal of Social Innovation, 2024)
A thermosyphon is a vacuumed metal tube or pipe, partially filled with a liquid as working fluid and sealed and exhibite a high effective conductance. When used in a solar collector, ite performance may be expressed in terms of the heat it transfere to the tank water at its condenser with the heat it absorbs from the sun at its evaporator. In this study a set of fifty-two thermosyphons, made from 19.05-mm diameter copper tubes with distilled water as the working fluid, were tested for performance as to how well these thermosyphons effectively transfer the heat absorbed from the sun to the tank water. The insolation, wind speed and the temperatures of the various key components of the solar water heater were recorded by a data logger every minute for the whole twenty four hour period. Heat gains and losses by the components were calculated in terms of the increase or decrease of temperatures. The results show that the thermosyphons are effective in transferring the heat it absorbs to the tank water. However, the results also show that when the condenser section of the thermosyphons were still at a higher temperature to that of the evaporator section, heat flowed back thereby ipsing the heat stored by the tank water.